Formation of Various Polymeric Films via Surface‐Initiated ARGET ATRP on Silicon Substrates. (21st February 2021) - Kim, Su Youn; Seo, Hyun Ji; Kim, Sunhee; Cho, Woo Kyung
Abstract : The growth of various polymeric films such as neutral, zwitterionic, and anionic ones was investigated over time from the initiator‐immobilized silicon substrates. The polymerization reactions were carried out under ambient conditions via activators regenerated by electron transfer atom transfer radical polymerization (ARGET ATRP) without any predeoxygenating process. Each of the examined polymeric films showed linear/exponential growth over reaction times according to the measurement of ellipsometric film thickness. The successful formation of various polymeric films was further proved by X‐ray photoelectron spectroscopy, contact angle goniometry, and measurement of surface free energies. We think that this study can provide a basis for other researches that require to graft polymers with the adjustable film thickness for modulating chemical/physical properties at interfaces. Abstract : We investigated the growth of polymeric films of neutral, zwitterionic, and anionic monomers over time via oxygen‐tolerant SI‐ARGET ATRP. The ellipsometric thickness of the examined polymeric films showed linear/exponential growth of the polymer brushes over time. The formation of the various polymeric films was clearly demonstrated by the analysis of surface wettability, surface chemical compositions, and surface free energies.